CFD analysis of scavenging process for dome headed piston in two-stroke cycle engine. (2018) - Kapopara, Jaydeep M.; Patel, Sachin M.; Solanki, Nitinkumar M.; Patel, Parth M.; Thaker, Rahul M.; Patel, Dhruv P.; Bariya, Vijay V.; Patel, Bhavesh A.; Patel, Nikul D.
Abstract: Finite volume method (FVM) has been implemented to envisage the influence of crank angle on pressure variation, turbulent kinetic energy and velocity distribution in two stroke engine. A three dimensional Fluent-Computational Fluid Dynamics (CFD) tool of ANSYS 15.0 was used to reveal these variations for increasing volume scavenging efficiency. Crank angle was varied from 86.25° to 300° for predicting behavior of exhaust gases in scavenging process. Highest volume scavenging efficiency was measured at crank angle of 300°. The results showed that volume scavenging efficiency highly depend on crank angle which will directly affect combustion process. By doing so, one can able to modify the configuration of intake ports and have better exhaust gas-charge out of the cylinder and drawing in a fresh draught of air or fuel/air mixture for the next cycle.